If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(9 + 1) + -5 = (2y + -2) Combine like terms: 9 + 1 = 10 3(10) + -5 = (2y + -2) Multiply 3 * 10 30 + -5 = (2y + -2) Combine like terms: 30 + -5 = 25 25 = (2y + -2) Reorder the terms: 25 = (-2 + 2y) Remove parenthesis around (-2 + 2y) 25 = -2 + 2y Solving 25 = -2 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 25 + -2y = -2 + 2y + -2y Combine like terms: 2y + -2y = 0 25 + -2y = -2 + 0 25 + -2y = -2 Add '-25' to each side of the equation. 25 + -25 + -2y = -2 + -25 Combine like terms: 25 + -25 = 0 0 + -2y = -2 + -25 -2y = -2 + -25 Combine like terms: -2 + -25 = -27 -2y = -27 Divide each side by '-2'. y = 13.5 Simplifying y = 13.5
| k-7=10k-16 | | x^3-4x^2+x-9=0 | | 3i+10=14i-12 | | n^2-81= | | 8y+20=16-12 | | 7/2x=-21 | | 6x-5=8x+13 | | e^2x=1/9 | | -54+12x=6(x-3) | | F=1/9k(d-n) | | 6-3/4x=9 | | 6a^2-10=422 | | 3/7=r/4 | | 8(r+3)=72 | | 47=-2-7x | | -1x-52=x^2+6x+6 | | -0.0018x^2+0.06x+1.5=0 | | 3/4x-9=8 | | -3/2x-6 | | 7-5[4-(6y-3)]= | | 9x^4-12x^3+6x^2=0 | | -1/6m=31 | | -4=+15+2 | | 6x^3-14x^2+7x-6=0 | | -0.36842p=-4 | | 1.5x+x=7.5 | | 485=5(x^3) | | -4+15+2= | | -2b(4b+1)-6b=-100 | | X^2+6x=-44 | | 6x^3-14x^2+6x-9y=0 | | -2(4b+1)-6v=-100 |